(untitled) (INNOVATIVE ECONOMY, 2019)
Makovoz O.S. STRATEGIC MANAGEMENT IN THE PROCESS OF CONSTRUCTION OF SYSTEMS OF ECONOMIC PROTECTION OF THE RESULTS OF ACTIVITIES OF AGRO-BUSINESS ENTITIES Purpose. The aim of the article is generalization of the conceptual foundations of strategic management to ensure the economic security of the enterprise in the process of building systems of economic protection of the results of activities of agro-business subjects as an effective mechanism for counteracting external and internal threats. Methodology of research. Scientific methods are used in the writing of the articles, in particular: theoretical generalization – to understand key theories of strategic management; synthesis and analysis – to detail the systems of economic protection of the results of the activity of the subjects of agribusiness as an object of research by its breakdown into parts; abstract and logical method – during the study of the structure of the components of the system of economic protection of the results of the enterprises. Findings. The toolkit of economic protection of agribusiness entities, which can be further transformed and supplemented according to the research of the peculiarities of functioning of their activity in the current market conditions, is investigated. It is substantiated that economic protection of the results of the enterprise activity should include a system of diagnostics and risk management, which will further ensure within the enterprise itself to make prompt decisions on strategic risk management both internal and external environment. The scheme of risk management in the system of economic protection of investment activities of agribusiness entities is proposed. The systems of economic protection of the results of activity of enterprises are improved. Originality. The main criteria of efficiency of economic protection of interests and results of activity of subjects of agro-business in the long term are substantiated: profitability of own capital and economic equilibrium, which characterizes rationality and prudence of management of economic resources and creates a basis for achievement of strategic goals of the enterprise in the long term. Practical value. The introduction of the proposed research results into the activities of agribusiness entities for the use of conceptual principles of strategic planning will contribute to the establishment of a system of economic protection of the results of business activity and dynamic development. Key words: strategic management; risk; threat; protection; result; economic security; management system; enterprise.